Efficient and photostable ternary organic solar cells with a narrow band gap non-fullerene acceptor and fullerene additive. Issue 14 (25th March 2020) - Lee, Jinho; Lee, Jong-Hoon; Yao, Huifeng; Cha, Hyojung; Hong, Soonil; Lee, Seongyu; Kim, Jehan; Durrant, James R.; Hou, Jianhui; Lee, Kwanghee
Abstract : The simultaneous enhancement of efficiency and photostability in organic solar cells is successfully achieved by introducing a fullerene acceptor as a solid additive into anon-fullerene bulk heterojunction system. Abstract : Recent breakthroughs in molecular design have allowed for remarkable achievement in the field of non-fullerene acceptor (NFA)-based organic solar cells (OSCs) with high power conversion efficiencies (PCEs) of over 15%. However, despite such promising advances, the inferior stability of OSCs under operating conditions remains a prominent challenge that must be overcome for their practical realization. Here, versatile ternary photoactive systems with simultaneously enhanced efficiency and photostability are developed by introducing a small amount of fullerene (PC71 BM) into a narrow band gap NFA-based bulk heterojunction nanocomposite (PTB7-Th:IEICO-4F); this approach leads to an enhanced PCE of 10.55% and a prolonged lifetime, retaining approximately 80% of the initial PCE after 500 h of operation under continuous illumination. Based on the energy levels and surface energies of the component materials, cascade energetic alignment facilitates electron transfer without trapping. The PTB7-Th/PC71 BM interface provides an energy barrier to suppress recombination between holes in PTB7-Th and electrons in IEICO-4F. Moreover, a small amount of PC71 BM promotes favorable molecular packing and orientation of IEICO-4F, leading to enhanced electron mobility and balanced charge transport. A study using transient absorption spectroscopy reveals that the ternary blend effectively suppresses the evolution of charge recombination.